Análise sócio-ambiental da bacia do rio Tambay na cidade de Bayeux-PB/Brasil - Alves, Déborah Melo (2012)
Knowing that water is welfar tor humanity, this work was advanced with objective of analize the problems socienviromental in basin of Tambay River in de ;Bayeux city Paraíba/Brazil. The crisis imminent of water well as the emergent crisis for aliments motivated of research that study in area there are agricultural cultivable. To development this research were applied questions with socioecomics in formation with communities profile determine in localized area Mesorregião of Wood Paraibana, Microregion of João Pessoa, in Bayeux, exactly in hydrographycic basin in Tambay River, containg Brazilian district, Tambay, Alto da Boa Vista, Jardim São Severino and Center, uses diverses of water were in period remarked realization of development, irrigation, deposition of garbage (liquid and solid) leisure, so than. There wasn t perceptible change in frame socioenviromental of basin. The garbage and sewer has as constant in the streets of districts. The quality of parameters that water analyzed were: choloride, demand biochemistry of oxygen, chemis try demand oxygen, nitrated, nitracit in group of metals considerate relevant (aluminium), pH, color, turbid, oxygen diluted, totals solid oils and shushes. The water Tambay River presentation in some cases analyses, values off limits determinate by resolution CONAMA 357/2005. Where values indicates by parameters, of oils and shushes, and so aren t permited by legislation to river 2nd degree. The river supracited, is polluted welfare deadly dirty in your course, that wood don t exist more and urban drainage was realized in direction river. Is explicit that associate of practices education enverometals together actions in direction to river, and sanitation are a resolution to problems in area.